Influence of public agricultural extension on technology adoption by small-scale farmers in Zimbabwe - Masere, Tirivashe P.; Worth, S. (2022)
This paper presents the findings of challenges facing Zimbabwe’s extension services and how these have affected the adoption of technologies they render to small-scale farmers. This study uses a critical review of relevant literature on Zimbabwe’s primary public extension agency (AGRITEX). Additionally, 21 key informant interviews (KIIs) were conducted to corroborate data collected in secondary research on extension approaches currently in use, the key factors affecting technology adoption, and the technology adoption process of small-scale farmers. The study found AGRITEX’s major challenges to be poor funding, poor remuneration and incentives for extension personnel, lack of in-service training, lack of appropriate technology, as well as poor operational resources like transport to reach all farmers. Consequently, services offered to small-scale farmers were compromised, which led to poor adoption of recommended technologies. Furthermore, the study determined that key factors influencing technology adoption are related to the farmers’ circumstances, the operating environment, and the attributes of technology itself. As a lasting solution to poor technology adoption, an adaptive extension system that promotes building the capacity of extension workers and researchers, as well as embracing farmers and their indigenous knowledge, is proposed.